Measuring Vestibular Contributions to Age-Related Balance Impairment: A Review - Wagner, Andrew R.; Akinsola, Olaoluwa; Chaudhari, Ajit M. W.; Bigelow, Kimberly E.; Merfeld, Daniel M. (Frontiers in Neurology, 2021)
Aging is associated with progressive declines in both the vestibular and human balance systems. While vestibular lesions certainly contribute to imbalance, the specific contribution of age-related vestibular declines to age-related balance impairment is poorly understood. This gap in knowledge is caused in large part by the inability to measure the specific age-related changes affecting the vestibular balance pathways. The purpose of this manuscript is to review the methods currently used to infer vestibular contributions to age-related imbalance.